2002
DOI: 10.1111/j.1346-8138.2002.tb00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Rising Incidence of Genital Herpes over Two Decades in a Sexually Transmitted Disease Clinic in North India

Abstract: Genital herpes, which was considered to be a minor sexually transmitted disease (STD) in the past in developing countries, is rapidly increasing; in contrast, bacterial STDs are declining. This changing trend of various STDs prompted us to analyze our data retrospectively to see whether a similar change is occurring in this part of India as well. The records of sexually transmitted diseases (STDs) clinic attendees from January 1977 to December 2000 were analyzed. The demographic profile of patients with genita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 17 publications
7
35
0
Order By: Relevance
“…An earlier report from the present institution observed a decreasing trend from 32.7% in 2006 to 14.8% in 2014 culminating in the present 5%. This is comparable to a study from Andhra Pradesh where too a decreasing tendency was noted ( years has been documented to rising in reports from studies from Chandigarh, Rohtak, North-eastern India, and even Kerala [8,13,29,30] In the present study 90% of the HSV cases were serologically detected again highlighting the common subclinical existences of this infection.…”
Section: Discussionsupporting
confidence: 89%
“…An earlier report from the present institution observed a decreasing trend from 32.7% in 2006 to 14.8% in 2014 culminating in the present 5%. This is comparable to a study from Andhra Pradesh where too a decreasing tendency was noted ( years has been documented to rising in reports from studies from Chandigarh, Rohtak, North-eastern India, and even Kerala [8,13,29,30] In the present study 90% of the HSV cases were serologically detected again highlighting the common subclinical existences of this infection.…”
Section: Discussionsupporting
confidence: 89%
“…8 A marked decline in bacterial STIs, resulting in an apparent increase in viral STIs, has been reported from different regions of India. [9][10][11] Our study confirmed a similar pattern of higher incidence of viral STIs which could be due to the increased usage of antibiotics. 10 Person with multiple sexual partner have higher risk of acquiring and transmitting STIs and risk increases many folds if they have sexual contact with commercial sex workers (CSWs) because CSWs are very important source of infection in our country as they are usually less educated and most of them don't know about STIs and also the people who visit them usually have less knowledge regarding use and benefits of barrier contraceptives.…”
Section: Discussionsupporting
confidence: 75%
“…[9][10][11] Our study confirmed a similar pattern of higher incidence of viral STIs which could be due to the increased usage of antibiotics. 10 Person with multiple sexual partner have higher risk of acquiring and transmitting STIs and risk increases many folds if they have sexual contact with commercial sex workers (CSWs) because CSWs are very important source of infection in our country as they are usually less educated and most of them don't know about STIs and also the people who visit them usually have less knowledge regarding use and benefits of barrier contraceptives. In our study, a significant higher STI prevalence was found in people with history of contact with multiple partners or visiting CSW as compared to people with no such history (p<0.05).…”
Section: Discussionsupporting
confidence: 75%
“…[5] An earlier study from Chandigarh has also shown a two-fold increase in its incidence (20.5% in 2000 vs. 11.4% in 1970). [18] A similar twofold rise (from 16.92 to 31.26%) was found in Rohtak from 2001 to 2006. [19,20] In north-east India also, it has increased in the last 10 years.…”
supporting
confidence: 67%